Συμπερίληψη σε λίστα με τους κορυφαίους ερευνητές παγκοσμίως - Karapanos, Evangelos (My University, 2026)
https://www.cut.ac.cy/news/article/?contentId=501840&fbclid=IwAR14yYwi46X4uk0lYQm2NpWaMjK0fmkK-A_NzgPYP_rwx45r5qQUdiFw5_8
Keywords: Sciences